What Is the Future of AI in Healthcare Delivery? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The healthcare landscape is in a constant state of evolution, driven by the relentless pursuit of improved patient outcomes, enhanced efficiency, and greater...
Keywords: AI in Medical Education and Future of Healthcare; Future; Healthcare; Delivery; Artificial Intelligence; Machine Learning; Deep Learning